Effects of supplemented Sauropus androgynus leaves powder on reproductive traits of Indonesian indigenous hens - Putranto, H. D.; Santoso, U. (Journal of the Indonesian Tropical Animal Agriculture, 2022)
The aim of this study was to analyze of Sauropus androgynus (SA) leaves powder supplementation on kampung hens reproductive traits. Forty kampung hens aged 4-5 months were distributed randomly into 4 treatments with 10 replications. A completely randomized design (CRD) was used as research design. Samples were placed in individual postal-litter system cages. The four groups were fed diets supplemented with 0, 4, 8, and 12% SA leaves powder for 8 weeks, respectively. The supplementation of SA leaves powder affected serum steroid hormone progesterone (P4) metabolite (P < 0.05), serum steroid hormone estradiol-17β (E2) metabolite concentration and a number of medium follicles yield significantly (P < 0.01). Concentration levels of serum steroid hormone E2 and P4 metabolites were 1 to 5-fold and 2 to 14-fold higher in supplemented hens than non-supplemented, respectively. In conclusion, supplementation of SA leaves increased serum steroid hormone E2 and P4 metabolite concentration, number, and weight of follicles. The role of precursor contained in SA leaves powder detected on Indonesia kampung hen’s reproductive traits.